Analisis Economic Value Added (EVA) Sebagai Alat Ukur Kinerja Keuangan PT Garuda Indonesia Tbk Tahun 2022-2024 - Eksa Dewi Rengganis; Sri Murwanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study was conducted to evaluate whether the company's financial performance has reached good standards using the EVA method at PT Garuda Indonesia Tbk for the 2022-2024 period. This study uses a quantitative descriptive approach and utilizes secondary data in the form of financial statements of PT Garuda Indonesia Tbk, which can be accessed through the company's official website or the Indonesia Stock Exchange (IDX). The subject of this study is PT Garuda Indonesia Tbk during the years 2022 to 2024. Performance measurement based on value creation uses the EVA method. The results of the study show positive EVA values for three consecutive years, indicating that PT Garuda Indonesia Tbk is able to create economic value for shareholders and provide a return that exceeds the cost of capital. Nonetheless, there are fluctuations in EVA values, signaling management to improve the efficiency of operational management and the company's capital structure.